Ecritures autobiographiques, remémoration et enjeux symboliques - Christine Plasse-Bouteyre (Conserveries Mémorielles)
A practice of writing so tied to recollection as autobiography cannot escape a sociological and historical questioning. The starting point of this article was a research that has brought us to study different aspects of autobiographies written par some professeurs de lettres of the Sorbonne between 1880 and 1940. We wish to understand how those scholars remember and represent themselves. We will focus ourselves on the status of the autobiography in the intellectual production of professors and on its symbolic, social and cultural dimensions. We wish to account for the social conditions of production of biographical discourses, the mental schemes guiding the presentation of the self and the self-definition of professors in writings of personal and recollective claim. It will consist of determining how the recollection, the perception and the representation of the self organize themselves and to understand the socially defined limits of what is possible and legitimate to write. Our objectives will therefore be to evaluate how these autobiographical productions constitute specific discursive practices, testamentary and commemorative discourses as statements revealing themselves through rhetorical and formal expressions and precise themes for which we can define the conditions of production and the social and symbolic effects.